Design and Simulation of Fuzzy Logic Based Temperature Control for a Plasma Nitriding Process. (2015) - Oltean, Stelian-Emilian; Dulău, Mircea
Abstract: The plasma ion nitriding is a multivariable process used for surface treatment. An important process parameter is the workpiece temperature in glow discharge. Due to the nature of the process containing nonlinearities and uncertainties, conventional control can be replaced with an advanced control based on intelligent systems. The paper contains the design of a fuzzy logic control of the workpiece temperature in a plasma ion nitriding process. The simulation diagram of the overall system was implemented and tested in Matlab/Simulink environment and uses a neural network model for the heating effect. The neural network model has been previously determined by using the practical knowledge and experimental data from different nitriding processes.